Methods Analysis for assessing the effectiveness of the air exchange organization - Dovgalyuk, V.; Sitnicka, A.; Tereschuk, M. (КНУБА, 2018)
This article provides the review of scientific literature on the estimation of ventilation systems efficiency. It has been shown that energy efficiency requirements are becoming increasingly important for building microclimate systems. The operating costs of ventilation and air conditioning systems in some buildings can reach 50% of the total cost. The state of the airspace directly affects the health of people and the productivity of their work. Therefore, the question of assessing the quality of ventilation and air conditioning systems at the design stage is relevant. There are different approaches to determining the efficiency of air exchange in the room. Modern approaches to assessing the effectiveness of ventilation in Ukraine, the EU and the US are significantly different, requiring an analysis and understanding of the advantages and disadvantages of each. The evaluation of the air exchange efficiency using the KL coefficient is based on the construction of an approximate mathematical model of heat and mass transfer processes in the room. The methods of its analytical determination are developed. However, the coefficient KL does not allow to evaluate the efficiency of ventilation systems with variable air flow, the use of KL is problematic for height uniform distribution of temperature in the room. European approaches to assessing the effectiveness of ventilation are based on the assessment of the average CO2 concentration in the room or the average concentration of CO2 in the service area. The concept of air "age" is also used. It is impossible to estimate the effectiveness of ventilation by the formation of temperature and humidity fields indoors according to European methods. US standards use indoor air quality and energy consumption to compare Evz ventilation efficiency. However, the determination of the efficiency of the air distribution Ez, on which the value of Evz depends, is carried out in a simplified manner. All existing techniques do not allow to determine the intensity of air turbulence in the room. For this purpose, we need to develop criteria for assessing the effectiveness of ventilation, which takes into account the majority of factors that affect the microclimate in the room.
Keywords: energy efficiency; ventilation systems; air conditioning; coefficient; flow rate; air "age"; American methodology; VAV-systems; single-channel systems; cold air supply